Społeczne doświadczanie przestrzeni. Socjologiczne studium wrocławskiego Nadodrza - Olejniczak-Brząkała, Paulina (2022)
Revitalization of urban space as means of renewing Polish cities is a relatively new phenomenon (Majer 2010). It consists of spatial, functional, economic, technical, environmental and most importantly social changes. Currently it is being stressed more and more often that all actions undertaken as part of the revitalization process should take into consideration the social aspect (Rogatka 2019:11). Based on this assumption, this thesis is an attempt to create a description of social experience of culture in the context of changes caused by revitalization as experienced by the inhabitants of the revitalized neighborhood of Nadodrze in Wrocław, Poland.Revitalization of Nadodrze is the first renewal project of this complexity and cost attempted in the city of Wrocław. Local authorities and the specialists working with them have created bold plans aimed at improving the socio-economic situation of the neighborhood and even the city as a whole (Gęsiarz 2014). Past negative reputation of this neighbourhood is more and more often giving way to narratives about the artistic, craft-oriented place which “(…) has made a huge, aesthetic civilisational jump forward” (Józefiak 2014). On the other hand, the new positive image of Nadodrze is sometimes contested by some inhabitants and social movements (Akcja Lokatorska 2013).The dissertation consists of four clearly distinguished chapters concerning: (1) identity, (2) quality of life, (3) civic participation of Nadodrze’s inhabitants, and (4) the perception of Nadodrze and its revitalization. Each chapter contains a theoretical study, a review of research results and a summary. The above-mentioned parts are preceded by an introduction which presents, i.a. how the considerations on local communities have changed over time and the methodology of own research. The thesis ends with a conclusion and an appendix.Analyses concerning the experience of Nadodrze by its inhabitants turned out to be multifaceted. The sense of identity with Nadodrze depends on the age of the residents and how long they have lived in the described area. The revitalization of Nadodrze has also contributed to the improvement of its image. The residents verify the narratives about Nadodrze by relating them to their own experiences and observations. The people living in the area are not by default2active participants in the revitalization process as much as they can occasionally become such. Instead of taking matters into their own hands (Szacki 1997), they expect agency mainly from the city authorities and entities associated with the municipality. Although in general neighborly contacts between the inhabitants should be considered superficial, there are events that are conducive to undertaking joint activities. The inhabitants of Nadodrze are aware of the revitalization process that has been taking place around them for several years and they perceive it mainly in the context of infrastructural changes. In general people living in the discussed area, non-governmental organizations, help oriented institutions as well as the broadly defined power holders like the municipality and developers can be counted among the beneficiaries of the changes associated with the revitalization process date are Nadodrze.
Keywords: space; identity; quality of life; civic activity; social capital; revitalization